ALLOCATIVE EFFICIENCY OF THE USE OF PRODUCTION FACTORS: EMPIRICAL STUDY ON RED CHILI FARMING IN PAKEM SUBDISTRICT - Adisa Putra Jaya (Faculty of Animal and Agricultural Science, Diponegoro University, 2021)
Chili production in Indonesia is increasing accumulatively, although the increase is not in such a large percentage. Generally, chili farming in Indonesia is a small-scale agricultural business on land use. The same applies to agricultural activities in Pakem Subdistrict of Sleman Regency. This research aimed to (1) determine the factors that affect chili production in Pakem Subdistrict of Sleman Regency, (2) determine the allocative efficiency of chili production factor in Pakem Subdistrict of Sleman Regency. The number of respondents selected in this study was 60 farmers. The research method uses Cobb-Douglas function analysis and allocative efficiency analysis. The results showed that land area factors and experience of farmers negatively affected the production of red chili. While the production factors of seeds, manure, insecticides, and labor positively affected chili production in Pakem Subdistrict. The allocative efficiency of the use of production factors indicates that the widespread use of land is inefficient while seeds, manure, insecticides, and labor are not yet efficient.